Amelioration of Cognitive Deficit by Moringa oleifera flower extract in a Scopolamine-Induced Alzheimer’s Disease-Like Condition in a Rat Model - sahu, Kantrol Kumar (Asian Journal of Pharmaceutics (AJP), 2025)
Alzheimer’s disease (AD) is the most prevalent form of dementia, marked by cognitive decline, amyloid-β (Aβ) accumulation, cholinergic dysfunction, neuroinflammation, and oxidative stress. Moringa oleifera flower (MOF) extract, rich in flavonoids, phenolics, vitamins, and calcium, has been traditionally recognized for its medicinal properties. This study explored the neuroprotective potential of MOF extract against scopolamine (SCO)-induced dementia in rats. Materials and Methods: Thirty Wistar rats were divided into five groups: Control (normal saline), SCO (3 mg/kg, i.p., days 15–21), MOF 200 + SCO, MOF 400 + SCO (administered orally for 21 days), and Donepezil (5 mg/kg, i.p., 21 days). Cognitive performance was assessed using the Morris water maze and Y-maze tests. On day 21, rat brains were collected for biochemical estimations (Aβ), acetylcholinesterase (AChE), nuclear factor erythroid 2-related factor 2 (Nrf-2), superoxide dismutase (SOD), reduced glutathione (GSH), and malondialdehyde (MDA), and histopathological analysis. Results: SCO administration significantly impaired memory, increased Aβ and AChE activity, suppressed Nrf-2 expression, and altered antioxidant defense by reducing GSH and SOD while elevating MDA levels. Pretreatment with MOF extract markedly improved cognitive performance, reduced Aβ and AChE activity, restored Nrf-2 expression, and normalized oxidative stress markers. Histopathological findings supported these protective effects. Conclusion: MOF extract effectively ameliorated SCO-induced cognitive impairments and oxidative damage, demonstrating its potential as a natural neuroprotective agent for the management of AD.